(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
Social studies educators need to understand the impact or assigned social action activities and service projects on student learning so they can best meet the goals of social studies education. A major goal of social studies education is to create good citizens, and a key aspect of being a good citizen is being civically engaged. Studies show that assigned social action activities and service projects can positively impact civic engagement in the areas of community issue awareness, character development, and social responsibility. Assigned social action activities or service projects should be utilized in the secondary social studies classroom to improve civic engagement and achieve a major goal of social studies education, creating responsible citizens.